Ten sessions of transcranial direct current stimulation for chronic chikungunya arthralgia: study protocol for a randomised clinical trial. Issue 10 (26th October 2022) - Nascimento, Abraão Sérvulo do; Cavalcante, Antônio Felipe Lopes; Araújo, Thiago Anderson Brito De; da Silva, João Danyell Dantas; Silva-Filho, Edson; Okano, Alexandre; Peroni Gualdi, Lucien; Pegado, Rodrigo
Abstract : Introduction: The chikungunya virus infection is still an epidemic in Brazil with an incidence of 59.4 cases per 100 000 in the Northeast region. More than 60% of the patients present relapsing and remitting chronic arthralgia with debilitating pain lasting for years. Transcranial direct current stimulation (tDCS) appears promising as a novel neuromodulation approach for pain-related networks to alleviate pain in several pain syndromes. Our objective is to evaluate the effectiveness of tDCS (C3/Fp2 montage) on pain, muscle strength, functionality and quality of life in chronic arthralgia. Methods and analysis: This protocol is a single-centre, parallel-design, double-blind, randomised, sham-controlled trial. Forty participants will be randomised to either an active or sham tDCS. A total of 10 sessions will be administered over 2 weeks (one per weekday) using a monophasic continuous current with an intensity of 2 mA for 20 min. Participants will be evaluated at baseline, after the 10th session, 2 weeks and 4 weeks after intervention. Primary outcome: pain assessed using numeric rating scale and algometry. Secondary outcomes: muscle strength, functionality and quality of life. The effects of stimulation will be calculated using a mixed analysis of variance model. Ethics and dissemination: The study was approved by the ethics committee of the Faculty of Health Sciences of Trairí, Federal University of Rio Grande do Norte (No. 2.413.851) and registered on the Brazilian Registry of Clinical Trials. Study results will be disseminated through presentations at conferences and publications in peer-reviewed journals. Trial registration number: RBR-469yd6.